2018
DOI: 10.1038/s41397-018-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of adverse drug reactions and potential for pharmacogenomic testing in Singaporean adults

Abstract: Adverse drug reactions (ADRs) contribute to hospitalization but data on its economic burden is scant. Pre-emptive pharmacogenetic (PGx) testing can potentially reduce ADRs and its associated costs. The objectives of this study were to quantify the economic burden of ADRs and to estimate the breakeven cost of pre-emptive PGx testing in Singapore. We collected itemized costs for 1000 random non-elective hospitalizations of adults admitted to a tertiary-care general hospital in Singapore. The presence of ADRs at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The consequences of ADRs have considerable importance in health economics. For instance, in Singapore, a study published in 2019 revealed that the economic burden of 81 admissions caused by ADRs cost US $570,404 ( Chan et al, 2019 ). Similarly, in Europe in 2016, the estimated direct costs of ADR in hospitals for the public care sector ranged from €2.8 billion to €84.6 billion ( Zsifkovits et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of ADRs have considerable importance in health economics. For instance, in Singapore, a study published in 2019 revealed that the economic burden of 81 admissions caused by ADRs cost US $570,404 ( Chan et al, 2019 ). Similarly, in Europe in 2016, the estimated direct costs of ADR in hospitals for the public care sector ranged from €2.8 billion to €84.6 billion ( Zsifkovits et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These costs were signi cantly higher for bleeding/elevated international normalized ratios compared to other ADRs, and for drugs acting on the blood coagulation system compared to other drug classes. [44] Similarly, in Europe in 2016, the estimated direct costs of ADR in hospitals for the public care sector ranged from €2.8 billion to €84.6 billion. [45] In 2012, Spanish authors conducted a systematic review and concluded that studies regarding ADR costs have heterogeneous designs.…”
Section: Discussionmentioning
confidence: 99%
“…Not only public health but also medical resources were affected. A team in Singapore observed higher laboratory costs in the residency of patients with ADRs (85).…”
Section: Pharmacogenomic Test For Prevention Of Severe Cutaneous Adverse Reactionsmentioning
confidence: 99%